Pengaruh Rasio Likuiditas, Aktivitas, Profitabilitas dan Kebijakan Dividen terhadap Nilai Perusahaan pada Perusahaan Sektor Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Ginting, Shelvia Agusta Br.; Gultom, Robinhot; Ginting, Mitha Christina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effect of liquidity, activity, profitability, and dividend policy on firm value in primary consumer goods companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The independent variables examined include liquidity as measured by the Current Ratio, activity as measured by Total Asset Turnover, profitability proxied by Return on Assets, and dividend policy represented by the Dividend Payout Ratio. Firm value is used as the dependent variable and is measured using Tobin’s Q. This research employs a quantitative approach using secondary data obtained from companies’ financial statements. The sample consists of 37 companies, resulting in 111 observations over the study period. The data analysis technique used is Structural Equation Modeling–Partial Least Square (SEM-PLS), which is suitable for analyzing complex relationships among variables. The findings reveal that liquidity and activity have a positive and significant effect on firm value, indicating that companies with better short-term financial capability and efficient asset utilization tend to have higher firm value. In contrast, profitability does not show a significant effect on firm value, suggesting that profit generation alone is not a determining factor for investors. Dividend policy is found to be insignificant at the 5% significance level but becomes significant at the 10% level, indicating a relatively weak influence. The Adjusted R-Squared value of 0.195 indicates that the model explains 19.5% of the variation in firm value